Solve for $x \in \mathbb{R}$

$$4x^2(x+2) +3(2x^2-4x-3)\sqrt{4x+3} +6x = 0$$

I tried taking square by isolating the radical, but the resultant equation couldn't be solved.

Any help will be appreciated.

  • $\begingroup$ I suspect you are expected to make an educated guess here by checking values of $x$ which cause $4x+3$ to be a perfect square. But then $x$ cannot be an integer since all odd squares are of the form $4n+1$. So $\frac{3}{2}$ would be a good first guess since $4\left(\frac{3}{2}\right)+3=9$. Checking this value verifies that it is a solution. To see if there are other real solutions would require eliminating the radical and applying perhaps Descartes Rule of signs and other tests. $\endgroup$ – John Wayland Bales May 4 '16 at 4:52
  • $\begingroup$ Confession: I actually tried $\frac{1}{4}$ first but it was not a solution. You would also check $-\frac{1}{2}$. $\endgroup$ – John Wayland Bales May 4 '16 at 4:57

Let $X=4x+3$. Then, $$3(2x^2-X)\sqrt{X}=-2x(2x^2+X)$$ Squaring the both sides gives $$9(2x^2-X)^2X=4x^2(2x^2+X)^2,$$ i.e. $$4x^4X-4x^2X^2+9X^3-16x^6+16x^4X-36x^2X^2=0$$ $$X(4x^4-4x^2X+9X^2)-4x^2(4x^4-4x^2X+9X^2)=0$$ $$(X-4x^2)(4x^4-4x^2X+9X^2)=0$$ since $9X^2=X^2+8X^2$ $$(X-4x^2)(4x^4-4x^2X+X^2+8X^2)=0$$ to have $$(X-4x^2)((2x^2-X)^2+8X^2)=0$$ finally, $$(-4x^2+4x+3)((2 x^2-4 x-3)^2+8 (4 x+3)^2)=0$$ and so $$x=\frac 32,-\frac 12.$$ The former is sufficient while the latter isn't. So, $\color{red}{x=\frac 32}$ is the only solution.

  • 1
    $\begingroup$ Excellent! (+1) $\endgroup$ – Henry May 4 '16 at 5:16
  • $\begingroup$ Hello Sir. Can you also help me with this question ? $\endgroup$ – Henry May 4 '16 at 5:35

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.